Efektivitas Google Classroom dan Literasi Digital dalam Meningkatkan Prestasi Mahasiswa Administrasi Perkantoran: The Effectiveness of Google Classroom and Digital Literacy in Improving the Achievement of Office Administration Students - Sudirman, Sudirman; Rinaldi, Muammar; Sutejo, Bambang (ITScience (Information Technology and Science), 2024)
The purpose of this study was to determine whether online learning using the Google Classroom application and digital media literacy affects the learning achievement of office administration education students at the Faculty of Economics. The population was 59 students, and the entire population was a sample. The instrument used was a questionnaire, so the data was analyzed using descriptive statistics. The data analysis techniques used in this study were the Validity Test, Reliability Test, Normality Test, Linearity Test, Multicollinearity Test, and T and F Test. Data processing using SPSS Version 25 obtained the results of the calculation of the value showing t count 3.925> t table 1.672 with a significance value of 0.000 <0.05, explaining that there is an effect of online learning based on Google Classroom on learning achievement. Then obtained tcount value 3.228> ttable 1.672 with a significance value of 0.002 <0.05, explaining that digital media literacy has a positive and significant effect on learning achievement and obtained Fcount 13.635> Ftable 3.16 with a significance value of 0.000 <0.05, explaining that online learning based on google classroom and digital media literacy on learning achievement has a positive and significant effect together on the learning achievement of Office Administration Education students Stambuk 2018 Faculty of Economics, State University of Medan. There is a positive and significant simultaneous influence between online learning based on Google Classroom and digital media literacy on the learning achievement of Office Administration Education Study Program Students.